Maturity trends for the Late Devonian Duvernay Formation and identification of the Willesden-Green Maturity High. (November 2022) - Yeates, David W.; Hockaday, William C.; Atchley, Stacy C.; Rau, Elisabeth G.; Thorson, Anna M.
Abstract: Maturity trends appearing in the literature for the Late Devonian Duvernay Formation within the Western Canada Sedimentary Basin (WCSB) are inconsistent and do not reflect hydrocarbon production. To address these inconsistencies and more accurately delineate Duvernay maturity trends, this study produces solid-state 13 C Nuclear Magnetic Resonance (NMR) spectroscopy and Rock-Eval Tmax data from 38 wells throughout the WCSB. The Duvernay is divided into three different assessment areas that include, from east to west, Innisfail, Willesden-Green, and Kaybob. Based upon the proportion of aromatic to aliphatic carbon of the source rock organic matter, the Duvernay maturity generally increases towards the southwest and mimics structural depth, except within the Willesden-Green area. The Innisfail area has the shallowest depths and only the southern portion reaches oil maturity. The Willesden-Green and Kaybob areas range from oil to dry gas maturity. Although Willesden-Green and Kaybob have similar structural depths (P = 0.24), they have a significant difference in solid-state 13 C NMR proportion of aromatic to aliphatic (P = 0.05) and Tmax values (P = 0.00). The average residuals from the depth vs solid-state 13 C NMR proportion of aromatic carbon and Tmax best fit line show an increase of 0.09 and 10 °C respectively in Willesden-Green compared to Kaybob. Maps of the maturity indicators show the increase in maturity within Willesden-Green is perpendicular to structural strike. This study names this anomalous feature the Willesden-Green Maturity High. Highlights: Comparison of aromatic and alkyl carbon via solid-state 13 C Nuclear Magnetic Resonance (NMR) is a maturity proxy. Published trends of Duvernay Formation thermal maturity are inconsistent and the 13 C NMR maturity proxy refines the trend. The Duvernay Formation within the Willesden-Green region is more mature than the Kaybob region, even at similar depths. The Willesden-Green Maturity High is oriented perpendicular to regional maturity trends that conform to burial depth. Solid-state 13 C NMR maturity indicators identify oil mature regions that were previously identified as immature.